2011
DOI: 10.1007/s00401-011-0911-2
|View full text |Cite
|
Sign up to set email alerts
|

p62 positive, TDP-43 negative, neuronal cytoplasmic and intranuclear inclusions in the cerebellum and hippocampus define the pathology of C9orf72-linked FTLD and MND/ALS

Abstract: Neuronal cytoplasmic inclusions (NCIs) containing phosphorylated TDP-43 (p-TDP-43) are the pathological hallmarks of motor neuron disease/amyotrophic lateral sclerosis (MND/ALS) and FTLD-TDP. The vast majority of NCIs in the brain and spinal cord also label for ubiquitin and p62, however, we have previously reported a subset of TDP-43 proteinopathy patients who have unusual and abundant p62 positive, TDP-43 negative inclusions in the cerebellum and hippocampus. Here we sought to determine whether these cases c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
367
6
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(409 citation statements)
references
References 34 publications
34
367
6
2
Order By: Relevance
“…Positive cases were defined where p62‐positive, TDP‐43‐negative NCI within either the cerebellum (see [8]) or hippocampus (see [7]) could be clearly seen under low power objective (×20) and the majority of high power fields (×40) contained at least two NCI. Either negative cases were completely devoid of p62 immunostaining, or small amounts of apparently extracellular and ‘extraneous’ p62‐positive particulate material was observed in occasional high power fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive cases were defined where p62‐positive, TDP‐43‐negative NCI within either the cerebellum (see [8]) or hippocampus (see [7]) could be clearly seen under low power objective (×20) and the majority of high power fields (×40) contained at least two NCI. Either negative cases were completely devoid of p62 immunostaining, or small amounts of apparently extracellular and ‘extraneous’ p62‐positive particulate material was observed in occasional high power fields.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the early pathological descriptions following the discovery of the C9ORF72 mutation indicated that the associated TDP‐43 pathology was usually type B, characterized by NCI in all cortical layers but with relatively few dystrophic neurites or neuronal intranuclear inclusions [7, 8, 9, 15]. However, more recent studies have frequently reported a significant proportion of C9ORF72 mutation cases to have other patterns of FTLD‐TDP, most often type A [9, 11, 15], and rarely type C [16].…”
Section: Introductionmentioning
confidence: 99%
“…30 TDP-43 inclusions are also prominent in cases linked to chromosome 9p 31 but HREM-specific pathology includes abundant cytoplasmic and intranuclear p62-positive inclusions in the hippocampus and cerebellum that are TDP-43-negative. 32,33 Precisely, how the HREM causes TDP-43 mislocalisation and neurodegeneration is not currently known. Evidence that the HREM reduces levels of C9ORF72 transcripts implicates a loss of function, however, probes detecting the HREM transcript identified RNA foci within the nuclei of neurons in the frontal cortex and spinal cord.…”
Section: Human_reference : Gcgcgctaggggccggggccggggcc---------------mentioning
confidence: 99%
“…conditions in which hippocampal pathology has been shown to play a role, such as in AD (Palop and Mucke, 2009), and C9orf72-related motor neuron disease and frontotemporal lobe dementia (Al-Sarraj et al, 2011;Cooper-Knock et al, 2012), as well as possibly chronic traumatic encephalopathy (CTE) (McKee et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%